2017
DOI: 10.1097/psn.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Among Patients After Day-Case Surgery

Abstract: Postoperative pain occurs at a high incidence after day-case surgery, with many patients reporting moderate to severe pain. A cross-sectional design was used in this study to estimate the prevalence of postoperative pain in the early postoperative period after day-case surgery and to determine whether there is a relationship between demographic and clinical variables. A convenient sample of 300 patients, aged between 18 and 80 years, was selected from all postoperative patients after day-case surgery over a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Table 1 displays the characteristics of the included studies, including study size, participant age range, surgery type, ambulatory vs inpatient setting, postoperative time points at which pain was assessed, and pain prevalence estimates. The 27 studies enrolled a total of 22,108 participants from: studies involving mixtures of different surgical procedures (n = 20 studies), 2 4 , 6 , 7 , 11 , 16 18 , 22 , 26 , 28 , 30 32 , 35 , 37 , 40 , 45 , 46 total knee replacement (n = 2 studies), 8 , 9 sternotomy (n = 1 study), 44 laparoscopic surgery (n = 1 study), 48 cataract surgery (n = 1 study), 39 orthopedic surgery (n = 1 study), 43 and routine dentoalveolar surgery (n = 1 study). 25 The 27 studies included ambulatory surgeries (n = 19), 3 , 4 , 7 , 11 , 16 , 17 , 22 , 25 , 26 , 28 , 30 32 , 35 , 37 , 39 , 40 , 46 , 48 inpatient surgeries (n = 1), 6 mixtures of both inpatient and ambulatory surgeries (n = 4), 2 , 18 , 43 , 45 or was not specified (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 displays the characteristics of the included studies, including study size, participant age range, surgery type, ambulatory vs inpatient setting, postoperative time points at which pain was assessed, and pain prevalence estimates. The 27 studies enrolled a total of 22,108 participants from: studies involving mixtures of different surgical procedures (n = 20 studies), 2 4 , 6 , 7 , 11 , 16 18 , 22 , 26 , 28 , 30 32 , 35 , 37 , 40 , 45 , 46 total knee replacement (n = 2 studies), 8 , 9 sternotomy (n = 1 study), 44 laparoscopic surgery (n = 1 study), 48 cataract surgery (n = 1 study), 39 orthopedic surgery (n = 1 study), 43 and routine dentoalveolar surgery (n = 1 study). 25 The 27 studies included ambulatory surgeries (n = 19), 3 , 4 , 7 , 11 , 16 , 17 , 22 , 25 , 26 , 28 , 30 32 , 35 , 37 , 39 , 40 , 46 , 48 inpatient surgeries (n = 1), 6 mixtures of both inpatient and ambulatory surgeries (n = 4), 2 , 18 , 43 , 45 or was not specified (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 9 , 44 Only one study specified whether the pain being assessed was at rest or with movement. 16 …”
Section: Resultsmentioning
confidence: 99%
“…Uncontrolled pain is typically one of the main reasons for delayed discharge in day surgery (Mitchell 2004, Rae 2016. Similarly, moderate to severe pain is commonly reported following discharge after day surgery (Elaqoul et al 2017) and previous studies have estimated that more than half of patients experience this level of pain in the first 24 hours of being home (Townsend & Cox 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The α value was set at 0.05, and power was set at 0.90. Based on our pretest research comparing patients' and nurses' pain scores, δ was 1.01 (and a change in one point in the NRS-based postoperative pain score indicates a clinically significant change (Elaqoul et al, 2017)) and σ was 1.91. We then looked up the appropriate sample size in the "twosample mean comparison t test-required sample size table," and we found that the sample size should be at least 58.…”
Section: Sample Sizementioning
confidence: 99%